The effect of community treatment orders on outcome as assessed by the Health of the Nation Outcome Scales - Kisely, S.; Xiao, J.; Crowe, E.; Paydar, A.; Jian, Le (2014)
Many studies of outpatient commitment have assessed effects on health service use rather than psychiatric symptomatology. We examined whether patients on one form of outpatient commitment, community treatment orders (CTOs), had better outcomes on the Health of the Nation Outcome Scales (HoNOS). Cases and controls from three linked Western Australian databases were matched on age, sex, diagnosis and time of hospital discharge. These databases cover the entire state (population=2.3 million). We compared HoNOS scores of CTO cases and controls at baseline, six-, and twelve-month follow-up, using multivariate analyses to further control for confounders. We identified 1296 CTO cases between 2004 and 2009 along with the same number of controls matched on age, sex, discharge date and mental health diagnosis (total n=2592). HoNOS scores were available for 1433 (55%) of the patients who could have had these recorded at baseline (748 CTO cases and 685 controls). There was no significant difference in HoNOS scores at six- and twelve-month follow-up between CTO cases and controls after adjusting for potential confounders at each time-point. Although the study was limited by missing data, outpatient commitment in the form of CTOs may not result in better psychiatric outcomes as measured by the HoNOS. © 2014 Elsevier Ireland Ltd.